Biomolecular Modulation of Neurodegenerative Events during Ageing. (25th October 2015) - Nebbioso, Marcella; Scarsella, Gianfranco; Librando, Aloisa; Pescosolido, Nicola
Abstract : The objective is to assess the modulation of retinal and optic nerve degenerative events induced by the combination of α -lipoic acid (ALA) and superoxide dismutase (SOD) in an animal model of ageing. For this study, 24 male Wistar-Harlan strain rats were left to age for up to 24 months. One group of rats was subjected to a diet supplemented with ALA and SOD for 8 weeks, while another group was used as a positive control and not subjected to any dietary treatment. To assess the cytoprotective effects of the antioxidants, a morphological analysis was carried out on sections of retina and optic nerve head, stained with haematoxylin-eosin, followed by an analysis of the modifications to nuclear DNA detected by the TUNEL technique. The lipid peroxidation assay was used to assess the damage induced by oxidative stress at cell membrane level. The molecules involved in apoptosis mediated by oxidative stress, such as caspase-3 and inducible nitric oxide synthase, were also assayed by immunolocalization and western blot. ALA and SOD are able to counteract senile neurodegenerative deterioration to the retina and optic nerve. Indeed, the combination of these antioxidant molecules can reduce oxidative stress levels and thus prevent both nuclear degradation and subsequent cell death.